Demographic Factors Influencing Learner Autonomy among Indonesian EFL Students: A Quantitative Study - Nurul Ashri (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This study explores how selected demographic factors, gender, language proficiency level, region of origin, faculty affiliation, and field of study relate to learner autonomy among English as a Foreign Language (EFL) students at Universitas Pamulang. Grounded in the constructivist view of learning and self-regulated learning theory, the research employed a quantitative survey using Biçer's (2017) Learner Autonomy Scale, with 80 students participating. Due to non-normal data distribution, non-parametric tests were used in the analysis. This study uniquely shows that only gender has a statistically significant effect on learner autonomy, with female students demonstrating higher autonomy in both planning and learning process dimensions. In contrast, no significant differences were found for the other demographic variables. These findings suggest that while some background characteristics like gender may influence learner autonomy, broader factors such as classroom practices, instructional design, and learner agency play a more central role. The study contributes to the EFL field by highlighting the limited role of static demographic factors and reaffirming the importance of pedagogical strategies that foster autonomy in diverse learner populations.